A method for the analysis of the oligomerization profile of the Huntington’s disease-associated, aggregation-prone mutant huntingtin protein by isopycnic ultracentrifugation - Bonavita, Raffaella; Di Martino, Rosaria; Cortone, Giuseppe; Prodomo, Antonello; Di Gennaro, Mariagrazia; Scerra, Gianluca; Panico, Valentino; Nuzzo, Silvia; Salvatore, Marco; Williams, Sarah V.; Vitale, Fulvia; Caporaso, Maria Gabriella; et al. (Frontiers in Molecular Biosciences, 2024)
Conformational diseases, such as Alzheimer's, Parkinson's and Huntington's diseases as well as ataxias and fronto-temporal disorders, are part of common class of neurological disorders characterised by the aggregation and progressive accumulation of mutant proteins which display aberrant conformation. In particular, Huntington's disease (HD) is caused by mutations leading to an abnormal expansion in the polyglutamine (poly-Q) tract of the huntingtin protein (HTT), leading to the formation of inclusion bodies in neurons of affected patients. Furthermore, recent experimental evidence is challenging the conventional view of the disease by revealing the ability of mutant HTT to be transferred between cells by means of extracellular vesicles (EVs), allowing the mutant protein to seed oligomers involving both the mutant and wild type forms of the protein. There is still no successful strategy to treat HD. In addition, the current understanding of the biological processes leading to the oligomerization and aggregation of proteins bearing the poly-Q tract has been derived from studies conducted on isolated poly-Q monomers and oligomers, whose structural properties are still unclear and often inconsistent. Here we describe a standardised biochemical approach to analyse by isopycnic ultracentrifugation the oligomerization of the N-terminal fragment of mutant HTT. The dynamic range of our method allows one to detect large and heterogeneous HTT complexes. Hence, it could be harnessed for the identification of novel molecular determinants responsible for the aggregation and the prion-like spreading properties of HTT in the context of HD. Equally, it provides a tool to test novel small molecules or bioactive compounds designed to inhibit the aggregation of mutant HTT.